Provincialising smart urbanism in Taipei: The smart city as a strategy for urban regime transition. (February 2021) - Chang, I-Chun Catherine; Jou, Sue-Ching; Chung, Ming-Kuang
The appeal of revolutionising urban governance through information technologies has prompted cities across the globe to pursue smart city initiatives. The mainstream scholarship on these initiatives has mostly focused on technology and corporate-led urban development, and it also often privileges the experience of cities in the global North. Nevertheless, this mainstream understanding of the smart city may obscure emerging new power dynamics and locally contextualised processes associated with smart urban development, especially in cities at the global periphery. Inspired by post-colonial theories, this article makes the case for 'provincialising' smart urbanism by dislodging technology from the centre of analysis, accentuating perspectives of cities outside the locations where the smart city knowledge is traditionally produced and attending to power relationships. In our case study of Taipei, this provincialising approach helps unveil various logics, intentionalities, assemblages and power dynamics through which the smart city is employed as a political strategy to facilitate urban regime transition. We argue that the current non-affiliated Ko administration exploits the veneer of technological superiority and political neutrality of its smart city agenda to set a new growth agenda, form new development coalitions, establish new institutions and incorporate rising populist momentum into policy-making. Focusing on the politics of being smart, our findings illustrate how smart city experiments reshape power dynamics and regime formation through reorganising actors and interest groups, reconfiguring government institutions, reallocating resource distribution and, in the end, bolstering governing legitimacy.